On the effect of biofouling on the minimum propulsion power of ships for safe navigation in realistic conditions. Issue 2 (18th February 2021) - Liu, Shukui; Papanikolaou, Apostolos; Bezunartea-Barrio, Ana; Shang, Baoguo; Sreedharan, Maya
Abstract: This study first examines the minimum power requirements of a tanker according to the IMO 2013 Interim Guideline (IMO 2013 ). For the estimation of the added resistance in waves a recently introduced semi-empirical method is used. Secondly, the influence of the increase in surface roughness of the hull and propeller due to fouling is investigated, reflecting the actual condition of a ship in service. The results show that even if ships are fulfilling the IMO 2013 Guideline, they may become unsafe in operation. Lastly, the uncertainties involved in the assessment procedure are discussed. The investigation conducted is particularly of interest for the assessment of the safety of ships now being idle or used as floating storage due to the impact of the pandemic COVID-19 on the world economy, while they are expected to go again into service once the demand for transport recovers.